Sleep, Pain Catastrophizing, and Central Sensitization in Knee Osteoarthritis Patients With and Without Insomnia. Issue 10 (October 2015) - Campbell, Claudia M.; Buenaver, Luis F.; Finan, Patrick; Bounds, Sara C.; Redding, Mary; McCauley, Lea; Robinson, Mercedes; Edwards, Robert R.; Smith, Michael T.
<x xml:space="preserve">Abstract</x> Objective Osteoarthritis (OA), a chronic degenerative joint disorder, is characterized by joint pain. Emerging research demonstrates that a significant number of patients evidence central sensitization (CS), a hyperexcitability in nociceptive pathways, which is known to amplify and maintain clinical pain. The clinical correlates of CS in OA, however, are poorly understood. Insomnia is prevalent in older adults with OA, and recent experiments suggest associations between poor sleep and measures of CS. Catastrophizing, a potent predictor of pain outcomes, has also been associated with CS, but few studies have investigated possible interactions between catastrophizing, sleep, and CS. Methods We conducted a case–control study of 4 well‐characterized groups of adults with insomnia and/or knee OA. A total of 208 participants completed multimodal sleep assessments (questionnaire, diary, actigraphy, and polysomnography) and extensive evaluation of pain using clinical measures and quantitative sensory testing to evaluate associations between CS, catastrophizing, and insomnia. Descriptive characterization of each measure is presented, with specific focus on sleep efficiency and CS. Results The knee OA–insomnia group demonstrated the greatest degree of CS compared to controls. In the overall sample, we found that catastrophizing moderated the relationship between sleep efficiency and CS. Specifically those with low sleep efficiency and high catastrophizing scores reported increased levels of CS. In addition, CS was significantly associated with increased clinical pain. Conclusion These findings highlight the importance of assessing sleep efficiency, CS, and catastrophizing in chronic pain patients and have important clinical implications for treatment planning.